An integrated strategy for evaluation of sulfur-fumigated edible herb Astragali Radix based on UPLC-MS/MS platforms and pharmacological analysis. Issue 12 (18th May 2021) - Ma, Guoxu; Luo, Zuliang; Yang, Meihua; Wu, Haifeng; Yang, Junshan; Xing, Xiaoyan; Sun, Xiaobo; Xu, Xudong
Abstract : Astragali Radix is an edible herb that has been employed in Traditional Chinese medicine (TCM) and has recently been recognized by various countries; however, it is also one of the most extensively sulfur-fumigated TCM components. Abstract : Astragali Radix is an edible herb that has been employed in Traditional Chinese medicine (TCM) and has recently been recognized by various countries; however, it is also one of the most extensively sulfur-fumigated TCM components. This study designed a UPLC-QTOF-MS/MS-guided isolation approach to generate sulfur-containing derivatives, and a novel sulfur-containing marker, namely, astragaloside sulfate, was characterized based on 1D and 2D NMR, which were derived from the main component of Astragali Radix, namely, astragaloside. Pharmacological experiments also showed that the activity of astragaloside decreased after it was converted into sulfate. Moreover, a rapid assay for the determination of astragaloside sulfate content by UPLC-QTRAP-MS/MS was established to evaluate samples that were non-fumigated and sulfur-fumigated at different levels. The method was applied to determine the content of JGS in the different batches of commercial samples. This research reveals that the practical procedure-based typical sulfur-containing indicator can be utilized for quality assurance of sulfur-fumigated and non-fumigated Astragali Radix .